THE SIGNIFICANCE OF SOCIAL CAPITAL FOR PSYCHOLOGICAL WELL-BEING EMPLOYEES - Blynova, Olena Yevhenivna; Kruhlov, Konstantyn Oleksandrovych (Insight: the psychological dimensions of society, 2019)
The article is dedicated to the study of the role and importance of the social capital in the psychological welfare of employees of the organization. The aim: the study of the social capital influence on the psychological welfare of employees of the organization. Methods. “Psychological welfare of the individual” by K. Riff in the adaptation of T. Shevelenkova and P. Fesenko by six scales: goals in life, positive relationships with others, personal growth, environment management, self-acceptance, autonomy. To measure the social capital as a certain set of resources that a person can get from his or her social network, the method “The questionnaire for measuring the social capital of the individual” by P. Styla in the adaptation of I. Semkiv was applied. Results. The psychological welfare is defined as experiences and states that point to the completeness of self-realization of a person in specific living conditions. The social capital is understood as a person’s social network, which is based on emotionally positive, trusting relationships and affects the improvement of the psychological comfort level of an individual. It has been established that the largest number of correlated relationships among the social capital scales has the “socio-professional resource”. Such results show the direct dependence of personal growth on one’s job availability, professional self-realization, productive communication with colleagues at work, ability to expand own social network, which is based on relationships of trust and mutual assistance. The fact is that the “productive skills” scale provides greater autonomy of the individual, that is, independence and self-sufficiency of the respondent, the ability to independently regulate his or her behaviour, which relies on one’s capabilities and abilities in building the strategy of behaviour and determining the vector of one’s life. Conclusions. The most significant resources of the social capital in the studied group of employees of the organization are “socio-professional resource”, “productive skills”, “emotional resource”. It was found that there are interconnections between the social capital resources of the individual and the indicators of his or her psychological welfare.